Effectiveness of the displacement-based seismic performance assessment for continuous RC bridges and proposed extensions. (15th October 2020) - Gentile, Roberto; Nettis, Andrea; Raffaele, Domenico
Highlights: An alternative DBA method for continuous deck bridges based on static analysis is proposed. An extension of the DBA to derive non-linear force-displacement curves is proposed. A stand-alone application to perform the above calculations is provided. The proposed method is as accurate as a pushover analysis and provides results within one standard deviation of time history analyses. Abstract: Seismic performance assessment of existing bridges, especially those designed without seismic criteria, is paramount in earthquake-prone countries. To perform this task, the Displacement-Based Assessment (DBA) represents a satisfactory trade-off between simplicity and accuracy. After describing the modal analysis-based DBA procedure, a static-based alternative is proposed in this paper, considering its strengths and limitations. Moreover, an extension of the procedure is proposed to derive the force-displacement curve of the bridge (pseudo-pushover capacity curve). The effectiveness of the DBA methodology, implemented via simplified mechanical models, is discussed through parametric analyses to address its practical applications. The DBA approach, both modal and static, is herein adopted for the transverse analysis of a set of 36 reinforced concrete continuous-deck bridges up to six spans, with pier height in the range 8–20 m and two different values of the deck transverse stiffness. Additional sensitivity analyses (24 case studies) are conducted to investigate the accuracy of the two approaches considering: 1) the length of the bridge, 2) the amount of longitudinal reinforcement in the piers; 3) different pier typologies. The results are compared to numerical pushover and time-history analyses using three suites of 10 scaled, natural ground motions respectively consistent with low-, medium- and high-seismicity sites. For the majority of the case studies, the resulting performance assessments fall within one standard deviation of the results of the time-history analyses. For this reason, the displacement-based modal or static approaches can represent a valid alternative to numerical non-linear static analyses for continuous bridges with six spans or less.